The Economics Students’ Belief, Perspective, and Challenges in Post Pandemic English Learning - Aisyah, Aisyah; Jumaroh, Jumaroh (Journal of Language Intelligence and Culture, 2024)
This study aims to obtain students’ beliefs, perspectives, and challenges in learning English through virtual learning after a year of pandemic in the Faculty of Economics and Business. The researchers examined the students’ perspectives and challenges of using WhatsApp group, Zoom, and Google Classroom based on their point of view. Also, in this study the students have given a chance to explore their opinion and some suggestions of the English learning process through the media stated. The researchers employed both qualitative and quantitative methods. They have distributed a questionnaire to collect the data. Fifty students were asked to fill a 5-point Likert scale questionnaire and answer one open-ended question. The researchers used Google Forms to facilitate the distribution and collection of data process. The findings stated half of the respondents, instead of joining the English class through media stated, they preferred joining the subject in the classroom. The other half surprisingly preferred learning English virtually. Both have their arguments supporting their perspectives.